Efficacy of Cognitive Training in Older Adults with and without Subjective Cognitive Decline Is Associated with Inhibition Efficiency and Working Memory Span, Not with Cognitive Reserve - López-Higes, Ramón; Martín-Aragoneses, María T.; Rubio-Valdehita, Susana; Delgado-Losada, María L.; Montejo, Pedro; Montenegro, Mercedes; Prados, José M.; de Frutos-Lucas, Jaisalmer; López-Sanz, David (Frontiers in Aging Neuroscience, 2018)
The present study explores the role of cognitive reserve, executive functions, and working memory span, as factors that might explain training outcomes in cognitive status. Eighty-one older adults voluntarily participated in the study, classified either as older adults with subjective cognitive decline or cognitively intact. Each participant underwent a neuropsychological assessment that was conducted both at baseline (entailing cognitive reserve, executive functions, working memory span and depressive symptomatology measures, as well as the Mini-Mental State Exam regarding initial cognitive status), and then six months later, once each participant had completed the training program (Mini-Mental State Exam at the endpoint) With respect to cognitive status the training program was most beneficial for subjective cognitive decline participants with low efficiency in inhibition at baseline (explaining a 33% of Mini-Mental State Exam total variance), whereas for cognitively intact participants training gains were observed for those who presented lower working memory span.